Application of Modified Humic Acid (MHA) Binder in the Pelletizing Of Fluxed Hematite Concentrate. (4th March 2017) - Zhou, Youlian; Wattanaphan, Pradchaya; Kawatra, S. Komar
ABSTRACT: Modified humic acid (MHA) binder consists of high molecular weight organic molecules and inorganic part. It is extracted from lignite coal with sodium hydroxide and used in pelletization of iron ore concentrates. Our previous study shows that MHA binder is also a potential binder instead of bentonite for pelletizing of fluxed hematite. For evaluating the use of MHA binder in pelletization of fluxed hematite, pelletizing tests were conducted to optimize parameters, such as dose, firing temperature and time. The results show that the qualities of green/dried balls with 0.6 wt% MHA binder are equal to or even better than that of 0.66 wt% bentonite pellets, and that both are much higher than the minimum requirements of the pellets' strengths. The compression strength of fired pellets also suggested that MHA binder is promising to completely replace bentonite in pelletizing of fluxed hematite concentrate. However, the abrasion rate of the fired pellets with MHA binder is slightly higher than that of bentonite pellets.